Transport of Toman Fish Seeds with Different Densities on 3 ppt Salinity Media - Nasir, Nasir; Iriansyah, Akhmad; Anwar, Rosadi; Akbar, Junius (Hasanuddin University, 2019)
Toman fish seeds (Channa micropeltes) generally come from natural catches in South Kalimantan and Central Kalimantan. A closed system is an effort to efficiency transportation costs by increasing the density of fish in transport media. Efforts to reduce stress levels are very important so that they can transport a lot, have small deaths, and take a longer time, and do not disturb the physiology of the fish after transportation. The purpose of this study was to determine the effect of giving 3 ppt salt in transport media to the survival of fish during transportation. This research consists of two stages of activity, that is stage one is transportation for 12 hours and stage two was post-transportation maintenance for 11 days. In stage one, the plastic bag is filled with 10 L of water and is packed according to the treatment. This study used a Completely Randomized Design (CRD) with 4 treatments 3 refitition to produce 12 experimental units. K treatment density of 30 heads / bag with no salt water (0 ppt) and treatment A: B: C with density (30: 50: 70) tail / bag with salt water (3 ppt). The calculation of the highest survival rate in treatment A was 97.80%. The results of analysis of varians (ANOVA) that the treatment has a real effect on survival rate in fish seed transport toman. This shows the best density in this study is 30 heads / bag. Keywords: redsnackhead Fish, Channa micropeltes, transportation, salinity